Drugs and their negative effects on the individual and society: a legal and social study (Entrepreneurship Journal for Finance and Business, 2024)
The issue of drugs is a pressing concern that is gaining increasing importance globally due to its profound impact on communities and individual health. Drug use leads to a wide range of negative effects, affecting both physical and mental health, resulting in chronic health issues such as depression, anxiety, and heart diseases. Additionally, drug use is associated with an increased risk of infectious diseases, such as HIV and hepatitis, particularly among youth populations.Furthermore, drug abuse contributes to family disintegration and rising crime rates, as addicts may resort to illegal activities to fund their habits, leading to an increase in thefts and other crimes. This phenomenon also erodes social relationships and heightens economic pressures on individuals and families.Research indicates that the economic costs resulting from drug use encompass healthcare burdens, increased spending on social welfare programs, and loss of productivity. Addressing these challenges requires a comprehensive response from all stakeholders, including governments, civil society organizations, and the private sector.This study reviews the social and economic impacts of drug use, providing a thorough analysis based on current research and studies. It also includes practical recommendations for improving prevention and treatment strategies, including enhancing collaboration among various institutions and developing effective educational and awareness programs.